1994
DOI: 10.1007/bf00126765
|View full text |Cite
|
Sign up to set email alerts
|

Diet overlap among size classes of Colorado River cutthroat trout (Oncorhynchus clarki pleuriticus) in a high-elevation mountain stream

Abstract: We examined the taxonomic composition, abundance, and size of food items consumed by young-ofyear, juvenile, and adult Colorado River cutthroat trout (Oncorhynchus clarki pleuriticus) in order to determine the degree of diet overlap occurring in a relatively unproductive, high-elevation, mountain stream. Overall, we identified 49 Families of insects representing nine Orders, and 4 other Classes of organisms in the diets of the trout sampled and saw no evidence of piscivory. Each size class of fish consumed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…There were slight increases in gastropod consumption with increased trout age at both sites and in chironomid consumption downstream. A similar small diet shift with age was observed in rainbow trout in a cold Arizona tailwater (McKinney and Speas 2001), and other studies have shown significant overlap in diets among different age classes of trout (e.g., Johnson 1981;Bozek et al 1994). Piscivory in the LRR was limited to four instances of cannibalism on age 0+ brown trout.…”
Section: Proportion Of Maximum Igrmentioning
confidence: 61%
“…There were slight increases in gastropod consumption with increased trout age at both sites and in chironomid consumption downstream. A similar small diet shift with age was observed in rainbow trout in a cold Arizona tailwater (McKinney and Speas 2001), and other studies have shown significant overlap in diets among different age classes of trout (e.g., Johnson 1981;Bozek et al 1994). Piscivory in the LRR was limited to four instances of cannibalism on age 0+ brown trout.…”
Section: Proportion Of Maximum Igrmentioning
confidence: 61%
“…Substantial overlap in diet and resulting potential for competition in the latter study was suggested as the primary mechanism of bull trout displacement by lake trout. Three size classes of Colorado River cutthroat trout O. clarki pleuriticus also demonstrated a similar degree of overlap (0.64 -0.87) in a high-elevation stream (Bozek et al 1994). The authors concluded food may be limiting in those unproductive streams and the high degree of overlap suggested strong intraspecific competition among size classes.…”
Section: Resultsmentioning
confidence: 92%
“…Johnson 1981;Bozek et al 1994). Significant overlap in diets among different age classes of trout has also been observed in other studies (e.g.…”
Section: Prey Utilisation Versus Available Benthosmentioning
confidence: 99%